Nursing care of a 71-year-old patient after ischemic stroke with thrombolytic treatment in the neurology department - Ryś, Bogusława; Bąk, Ewelina; Sajdok, Edyta (Quality in Sport, 2024)
Ischemic stroke is one of the most common causes of death and the main cause of permanent disability in the world’s population. Early detection of symptoms and appropriate treatment can significantly reduce the rate of deaths and/or reduce the risk of severe disability. The following study describes the case of a 71-year-old man who avoided partial or severe disability thanks to a quick reaction, accurate diagnostics and subsequent initiation of thrombolytic treatment.